Impact of Trade, Remittance and BOP on the Economic Growth of Nepal: An Autoregressive Distributed Lagged (ARDL) Bound Testing Model - Acharya, Santosh (Khwopa Journal, 2024)
This article explores the impact of trade openness, remittance, and BOP on the real GDP in Nepal. This research uses the ARDL Bound Testing model, considering the secondary data collected from the Ministry of Finance, which ranges from 1990 to 2022. This research aims to identify the impact of the external sector on the country's economic growth. The result establishes that BOP has adverse short and long-term effects on the country's economic growth, which indicates the variable's sensitivity. The trade openness rate also has a negative impact; however, remittance positively affects the long run. Hence, the government of Nepal should focus more on rationalising the remittance for the country's economic growth. However, on the other hand, working on trade policy should be a broad discussion to mitigate the negative impact on the country's economic growth.